Aportació a la biografia de Joan Roís de Corella: noves dades sobre el seu naixement i la seua mort - Chiner Gimeno, Jaume J. (Caplletra. Revista Internacional de Filologia, 2015)
On the basis of a testament until now considered as lost, the author offers new documental evidence on Joan Roís de Corella's date of birth. This new information is particularly relevant at a moment when Corella's influence on writers, like for instance Joanot Martorell, is very much under scrutiny.